2014
DOI: 10.1002/marc.201400455
|View full text |Cite
|
Sign up to set email alerts
|

Photopiezoelectric Composites of Azobenzene‐Functionalized Polyimides and Polyvinylidene Fluoride

Abstract: Light is a readily available and sustainable energy source. Transduction of light into mechanical work or electricity in functional materials, composites, or systems has other potential advantages derived from the ability to remotely, spatially, and temporally control triggering by light. Toward this end, this work examines photoinduced piezoelectric (photopiezoelectric) effects in laminate composites prepared from photoresponsive polymeric materials and the piezoelectric polymer polyvinylidene fluoride (PVDF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Further investigations aiming to reduce the energy dissipation should be carried out through direct integration of the photoactuator with piezoelectric material into a monolithic structure. To our best knowledge, this is the first report on the photoelectric energy conversion device from light energy to electric energy using a self‐oscillating polymer composite film, which is different from the previously reported photopiezoelectric composite film . This work provides new direction of the polymer actuators for applications in automated systems and energy ‐harvesting fields.…”
Section: Resultsmentioning
confidence: 65%
“…Further investigations aiming to reduce the energy dissipation should be carried out through direct integration of the photoactuator with piezoelectric material into a monolithic structure. To our best knowledge, this is the first report on the photoelectric energy conversion device from light energy to electric energy using a self‐oscillating polymer composite film, which is different from the previously reported photopiezoelectric composite film . This work provides new direction of the polymer actuators for applications in automated systems and energy ‐harvesting fields.…”
Section: Resultsmentioning
confidence: 65%
“…[ 19–22 ] Combining light‐driven LCN films combined with piezoelectric materials, such as PVDF, can further convert mechanical motions to electrical energy. [ 23–26 ] Wei et al reported a near‐infrared (NIR) light‐triggered generator composed of a liquid crystal elastomer (LCE) and PVDF film. [ 26 ] Tang et al reported an optical pendulum generator that could generate electricity continuously by liquid crystalline actuators’ oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…Smart systems belong to the group of materials capable of changing the basic properties, when they are exposed to external stimuli such as electric [1][2][3], magnetic [4,5], thermal [6,7], pH [8,9], or light [10,11]. In case of light stimulation, such smart systems can exhibit the shape [12] or resistivity [13] change or generate electric output [14].…”
Section: Introductionmentioning
confidence: 99%